Cleome gynandra: A wonder climate-smart plant for nutritional security for millions in semi-arid areas - Mashamaite, Chuene Victor; Manyevere, Alen; Chakauya, Ereck (Frontiers in Plant Science, 2022)
Spider plant (Cleome gynandra) is predominantly used as a traditional leafy vegetable throughout Africa and is considered a rich natural source of essential nutrients such as vitamins, minerals and proteins. With the increase in malnutrition, diet related non-communicable diseases and poverty across the continent of Africa, the spider plant is a bona fide alternative healthy food crop to alleviate these challenges. Spider plant is an erect annual herb that could grow up to 150 cm tall, strongly branched, with a long taproot and few secondary roots. It is commonly consumed in resource-poor communities especially during times of major food scarcity. It is a drought-tolerant and resilient annual vegetable crop capable of growing well in a wide range of climatic and edaphic conditions. Despite the potential benefits and wide adaptability, progressive attempts towards the development of C. gynandra as a crop have been impeded by issues like low investment in research and development resulting in poor seed quality, relatively low yields and susceptibility to pests and diseases. In this paper, we reviewed the research that has been done regarding its morphology, growing conditions, production and utilisation (i.e., nutrition). The current review highlighted the status of the science in advancing the domestication of C. gynandra as a potential power crop for several African countries. The review concluded that with the advancement of modern biotechnology techniques and genome sequencing, there is a compelling case for investment and development in C. gynandra as a candidate for managing micronutrient deficiencies during the post-pandemic era. Finally, the existing knowledge gaps (e.g., breeding) that necessitate explorations were identified and recommendations that could enhance its development and potential commercialisation were made.